Performance Analysis and Working Fluid Selection of a Supercritical Organic Rankine Cycle for Low Grade Waste Heat Recovery - Yourong Li; Shuangying Wu; Xiaoxiao Xu; Chao He; Chao Liu; Hong Gao (Energies, 2012)
The performance analysis of a supercritical organic Rankine cycle system driven by exhaust heat using 18 organic working fluids is presented. Several parameters, such as the net power output, exergy efficiency, expander size parameter (SP), and heat exchanger requirement of evaporator and the condenser, were used to evaluate the performance of this recovery cycle and screen the working fluids. The results reveal that in most cases, raising the expander inlet temperature is helpful to improve the net power output and the exergy efficiency. However, the effect of the expander inlet pressure on those parameters is related to the expander inlet temperature and working fluid used. Either lower expander inlet temperature and pressure, or higher expander inlet temperature and pressure, generally makes the net power output more. Lower expander inlet temperature results in larger total heat transfer requirement and expander size. According to the screening criteria of both the higher output and the lower investment, the following working fluids for the supercritical ORC system are recommended: R152a and R143a.